JKL-Ökobilanz - monetär bewerteter Ökobilanzansatz - Kurki, Hannu (1998)
This study focuses on environmental accounting, especially on environmental reporting of companies, which has been increasing through the 1990' s. Although the reporting activity has increased considerably, the content of the reports has been developing rather slowly and qualitative information still plays a central role in these reports. The main goal of this study is to develop a new model for environmental reporting, a model which would serve as a measure of the level of the environmental protection of a company. Before development of this new model, an analysis of the weak points of the current environmental reporting practices was conducted. As a result, e.g. the comparability and understandability of these reports was found rather poor. In earlier studies it has been shown that extensive use of ecobalances contributes to German companies' leading position in environmental reporting. Nevertheless, German reports also need further development in order to build a measure of the level of environmental protection activity. The new model for the environmental reporting (JKL-Ecobalance) is based on the ecobalance concept. Although the theoretical ecobalance concept consists of three parts (inventory analysis, impact analysis and valuation), only inventory analysis is actually used in reporting. The other two parts are usually completely ignored, which weakens the understandability and comparability of reported information. Thus the new model is developed in two phases. In the first phase, the focus is on developing the way of presenting inventory analysis information. This is done in order to improve the understandability of reported information, specifically for cases where valuation is ignored. This study's contribution include a classification of the material and energy flows according to their environmental effects and an arrangement of these effects according to their chronological and geographical realization. The second phase involves the development of a new valuation method based on environmental protection costs. This method abandons the valuation of environmental benefits and losses and substitutes them with environmental cost proxies, which are calculated from the actual costs of correction of environmental harms. The first step in the valuation is to calculate the unit costs for reducing different environmental harms. The calculation is based on the actual costs and the achieved reduction of pollution by environmental protection activities. The second step is to set the level that should be achieved by companies' environmental protection activities. In defining the level, the concept of "hoped-for-future" has been operationalized. This has been done by making minor changes to the method of Environmental Impact Assessment. The last step of the proposed valuation method is to calculate the aspired decrease of pollution and to multiply this figure by the calculated unit costs. The resulting figure reflects the cost of investments needed to act in accordance with the "hoped-for-future" set by society. Therefore the figure can be understood as the environmental debt of the company. One of the major advantages of this valuation method is that it makes the cost advantages gained by neglecting environmental protection activities transparent. Furthermore, the implementation of the site-specific Life Cycle Assessment based on the JKL-Ecobalance has been discussed in this study. The advantages of this kind of LCA are a better quality and validity of the presented information. Such implementation of LCA would also decrease the cost of collecting information.